ELEMENTARY EDUCATION OBSERVATORY – LITERACY AND INITIAL ELEMENTARY EDUCATION GRADE AND THE PEDAGOGICAL PRACTICES LABORATORY IN THE SOUTH AND SOUTHEAST REGIONS OF THE STATE OF PARÁ - Pereira dos Anjos, Cleide (Revista Gênero e Interdisciplinaridade, 2025)
The research and extension project, entitled “Elementary Education Observatory — Literacy and Early Years of Elementary School”, as well as the pedagogical practices laboratory, is a space for conducting studies and research on literacy and early years of elementary school, and can also be used to develop classes for these same grades in different territories in the southern and southeastern regions of the state of Pará. Our general objective is to create an elementary education observatory, as well as a pedagogical practices laboratory, for studies, research and extension activities within the scope of the Federal University of Southern and Southeastern Pará (UNIFESSPA). As a methodological reference, we chose bibliographical research and participatory research, and work projects as activities to be developed in the classroom. Regarding the production of classes, we inserted work projects into the pedagogical work within a line of research based on the historical-critical perspective and grounded in pedagogical praxis. As a result of our work, we have created a study and research group, which carried out bibliographic research with the study and discussion of sixty works in the area of ​​education; the production of a scientific article; six reading projects; and six work projects involving regional issues, such as culture, sociopolitical issues of agrarian reform settlements, indigenous villages and quilombola communities. The practical extension activities are the result of our research and part of the pedagogical praxis actions within the public school in the region.